AB0533 Pattern of drug use in systemic lupus erythematosus in real world clinical practice. (12th June 2018) - Costa, T.; Eusébio, M.; Falcão, S.; Araújo, F.; Nero, P.; Inês, L.; Rodrigues, M.; Jesus, D.; Barreira, S.; Macieira, C.; Cabral, M.; Sequeira, G.; et al.
Abstract : Background: Pharmacological treatment for systemic lupus erythematosus (SLE) is aimed at reducing disease activity, preventing flares and minimising the damage. The use of medication varies widely and therapeutic strategies are well defined only for certain organ manifestations. Hydroxychloroquine is the standard treatment for most SLE patients during the entire disease course, while immunosuppressants are recommended for those with severe organ involvement. Belimumab is the only biological currently licensed for SLE, although others are used off-label in clinical practice. Objectives: To describe the real-world patterns of drug use in SLE patients, and their relationship with disease phenotype. Methods: Observational study of adult SLE patients registered in the Rheumatic Diseases Portuguese Registry, who have clinical diagnosis of SLE, followed for at least 1 year and with available data on medication, which was retrieved. Sociodemographic and clinical characteristics were compared among treatment groups defined as: group 1 antimalarials and/or glucocorticoids; group 2 immunosuppressants (azathioprine (AZA)/mycophenolate mofetil (MM)/methotrexate (MTX))±antimalarials and/or glucocorticoids; group 3 biologics±immunosuppressants and/or antimalarials and/or glucocorticoids. To assess possible differences between the groups, univariate regression analyses were made. In all analyses significance level was set at 0.05. Results: A total of 824 SLE patients were included, mean age of 47.3±14.4 years, 92.3% female. The mean age at first symptoms was 31.6±14.1 and at SLE diagnosis of 34.1±14.3 years. On their last assessment, 678 (82.3%) were being treated with antimalarials, 463 (56.2%) glucocorticoids, 343 (41.6%) immunosuppressants (149 AZA, 99 MM, 67 MTX, 14 cyclosporine, 11 cyclophosphamide, 3 leflunomide), 53 (6.4%) biologics (32 rituximab, 21 belimumab) and 26 (3.2%) were off medication. The sociodemographic and clinical characteristics according to treatment groups are shown in table 1. Gender distribution was similar across groups. A high prevalence of women, Caucasians, non-smokers, acute cutaneous lupus and arthritis was found in all groups. Patients in group 1 had lower disease activity measured by SLEDAI, less organ damage measured by SLICC and lower physician's global assessment. In group 2 patients were younger and had higher prevalence of renal involvement. Patients in group 3 had higher SLEDAI score and damage, higher prevalence of mucocutaneous, articular, neurologic and hematologic involvement and more use of glucocorticoids. Conclusions: Almost all SLE patient with established disease were chronically medicated, most with antimalarials and/or glucocorticoids. As expected, group 1 had less severe disease. Patients under immunosuppressants had a higher frequency of renal involvement, which denotes a targeted therapeutic strategy. In routine clinical settings biologics are rarely used, being restricted to patients with very active SLE and multiple clinical manifestations. Disclosure of Interest: None declared